Asr suresi ışığında mutluluk prensipleri - Şahin, Abdurrahman (My University, 2006)
Asr Suresi Kur’an’ın en kısa ve özlü sürelerindendir. Kısa oluşuyla beraber Kur’an’ın özeti gibidir. İnsanı dünya ve ahirette hüsrandan ( zarardan ) kurtarıp mutluluğa kavuşturan dört temel prensip bu surede birarada verilmiştir. Bu prensipler şunlardır : 1-İman ( Allah’a inanmak ) 2-Salih Amel ( Allahı hoşnut eden iyi ve güzel davranışlar ) 3-Hakkı tavsiye etmek ( Başkalarına Allah’ı, adaleti, doğruluğu ve gerçekleri anlatmak, iyilikleri emretmek, kötülüklere engel olmak ) 4-Sabrı tavsiye etmek = İyilikleri emredip, kötülüklere engel olma görevini yaparken karşılıklı yardımlaşma ve dayanışma içinde olmak.

“Asr” is one of the shortest and most substantial suras of the Quran. However the shortness, it is like a brief of Quran. Four fundamental principles which attains happines for the human being by saving them from discouragment (loss) have been gathered in this sura. These principles are as follows: 1-Faith ( to have faith in Allah ) 2-Healty Action ( Good and fine behaviours pleasing “Esmaü’l-Hüsna” ) 3-Advise the right things ( to narrate to the others Allah, the justice, rightness and the truths, and to instruct the goodness and hinder the badness, ill behaviour.) 4-Advise the patience ( to be in mutual helping and acting in solidarity while instructing the goodness and hindering the badness )
Keywords: Asr Suresi; İslam Dini_Ayetler ve sureler (Kur’an); Tefsir